الإسلام والايمان والكفر من منظور قراني -دراسة تحليلية - عكاب حيدر خزعل فهد (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
It is no secret to those with bright minds and new minds that the words of the Holy Qur’an are completely consistent with what sound logic and the right approach say, and this harmony makes the meanings flow where the words are similar in their expressions without doubt or suspicion. The meaning is where the word indicates it. Among those words that have divergent meanings in the view of one group of minds, and are in agreement in the view of the other group, are the words Islam, faith, and disbelief, and the divisions that lie beneath them that lead to an independent understanding of each of them after seeking help from the same Qur’anic texts. This study, with its discussions and demands, presents the concepts of Islam, disbelief, and faith, and their derivations in the Holy Qur’an, and the concepts and meanings that fall under them that lead to the desired understanding, which the researcher presented in a brief manner. This research is concerned with studying these three terms and their semantic dimension, and revealing the Qur’anic meaning of each of them because of their importance in the field of doctrine as well as jurisprudence. The research is divided into three chapters, the first of which deals with the term “Islam,” as it works to reveal its linguistic dimension and its terminological dimension. Then, it crystallizes the Qur’anic vision for this term by examining the verses in which the word (Islam) or what is derived from it is mentioned, while paying attention to the contextual environment in which it appears. As for the second chapter, it examines the meaning of (faith) linguistically and terminologically, and contextually in the Holy Qur’an. Secondly, it follows the connotations of the term (faith). Based on what was stated in the noble verses, he concluded by determining the moral value of this term according to the Qur’anic context. As for the third chapter, it is sufficient to investigate the meaning of disbelief, as it traces the meaning of disbelief according to what is stated in the language and terminology, and then branches out to diagnosing its Qur’anic meaning through investigating it in its Qur’anic environment. The research ends by highlighting the results that resulted from it, supported by the sources and references relied upon in the study.